Periodic cycles of pneumococcal serotypes carried by children before and after 7-valent pneumococcal conjugate vaccine - Paulo, Ana Cristina (PLoS One, 2017)
BACKGROUND: Periodic cycles in the serotype-specific incidence of invasive pneumococcal disease have been described but less is known in carriage. METHODS: We analyzed serotype carriage prevalence among children 0–6 years old over a 15-year period that included pre-PCV7 data and a decade of PCV7 use. Mixed generalized additive models were used to study periodic cycles and how PCV7 impacted on them. RESULTS: Pneumococcal carriage data of 7,463 children were analyzed. Periodic cycles ranging from 3 to 6 years were observed for PCV7-serotypes (VT) 14, 19F and 23F and for non-PCV7 types (NVT) 3, 6A, 6C, 11A, and NT. An indirect impact of PCV7 on periodic cycles of NVT was observed and could be translated in three ways: (i) a higher amplitude in the PCV7 period (serotypes 3 and 11A), (ii) sustained increase in the prevalence of carriage (serotypes 6C, 19A and NT) and (iii) an increase in the inter-epidemic period (serotypes 3, 6A and NT). An increase in the child’s mean age of carriage of VTs 6B, 19F and 23F was observed. Serotypes 3, 6C, 11A and 15A became more frequent in ages previously associated with carriage of VTs. CONCLUSIONS: Periodic cycles among serotypes frequently carried exist and can be modeled. These cycles can be perturbed upon introduction of PCVs and can lead to shifts in the mean age of carriage. Cyclic re-emergence of VTs can occur in settings with non-universal vaccine use. These results should be taken into account when interpreting surveillance data on pneumococcal carriage.